Despite genetic isolation in sympatry, post-copulatory reproductive barriers have not evolved between bat- and human-associated common bedbugs (Cimex lectularius L.) - Sasínková, Markéta; Balvín, Ondřej; Vandrovcová, Jana; Massino, Christian; Weig, Alfons R; Reinhardt, Klaus; Otti, Oliver; Bartonička, Tomáš (Frontiers in zoology, 2023)
BACKGROUND: The common bedbug Cimex lectularius is a widespread ectoparasite on humans and bats. Two genetically isolated lineages, parasitizing either human (HL) or bat (BL) hosts, have been suggested to differentiate because of their distinct ecology. The distribution range of BL is within that of HL and bedbugs live mostly on synanthropic bat hosts. This sympatric co-occurrence predicts strong reproductive isolation at the post-copulatory level. RESULTS: We tested the post-copulatory barrier in three BL and three HL populations in reciprocal crosses, using a common-garden blood diet that was novel to both lineages. We excluded pre-copulation isolation mechanisms and studied egg-laying rates after a single mating until the depletion of sperm, and the fitness of the resulting offspring. We found a higher sperm storage capability in BL, likely reflecting the different seasonal availability of HL and BL hosts. We also observed a notable variation in sperm function at the population level within lineages and significant differences in fecundity and offspring fitness between lineages. However, no difference in egg numbers or offspring fitness was observed between within- and between-lineage crosses. CONCLUSIONS: Differences in sperm storage or egg-laying rates between HL and BL that we found did not affect reproductive isolation. Neither did the population-specific variation in sperm function. Overall, our results show no post-copulatory reproductive isolation between the lineages. How genetic differentiation in sympatry is maintained in the absence of a post-copulatory barrier between BL and HL remains to be investigated.
Keywords: Host adaptation; Ecological speciation; Host fidelity; Sperm storage